Neither, either, or both? Who sees GM and non‐GM food labels?. Issue 4 (11th October 2022) - Kolodinsky, Jane; Buzas, Jeffrey; Rose, Nick; Zheng, Yuqing
Abstract: The US National Bioengineered Food Disclosure Standard mandates disclosures on foods containing genetically modified (GM) ingredients, while allowing voluntary non‐GM claims to coexist in the marketplace. Using cross‐sectional survey data, accounting for error term correlation and controlling for demographic variability, we describe the types of GM food labels seen by respondents and quantify the association of other label reading behaviors and demographic characteristics on seeing GM and/or non‐GM labels. The percent of respondents seeing both contains and does not contain GM labels increased between 2018 and 2021, with more respondents seeing non‐GM compared with contains GM labels each year. Estimated conditional probabilities reveal that time, other label reading behaviors, and attitudes are heterogeneously associated with seeing contains GM and non‐GM labels.